Restriction endonuclease‐mediated real‐time digestion‐PCR for somatic mutation detection. Issue 12 (13th December 2012) - Zhao, Jinyin; Xie, Feifei; Zhong, Wei; Wu, Weili; Qu, Shoufang; Gao, Shangxian; Liu, Licheng; Zhao, Jing; Wang, Mengzhao; Zhou, Junyi; Jie, Huang; Chen, Weijun
Abstract PCR is a powerful platform for clinical and diagnostic applications, but challenges remain in detecting somatic mutations, as mutant cells are often mixed with more numerous wild‐type cells at the tissue‐sample sites. Here, we describe a novel method that couples PCR with restriction endonuclease digestion (designated real‐time digestion‐PCR, or RTD‐PCR) in a one‐step reaction tube for detecting somatic mutations from a minority of cells. The PCR mixture contains a thermostable restriction enzyme that digests wild‐type alleles during the PCR program, allowing selective amplification of the mutant alleles. To validate this method, we used real‐time digestion‐PCR for the specific detection of the EGFR (epidermal growth factor receptor) treatment resistance‐inducing mutation, T790M, combining with three different platforms: Sanger sequencing, TaqMan probe PCR and Sequenom MassArray. From 78 clinical samples, seven T790M mutations were consistently detected on all three platforms, indicating that RTD‐PCR may be a useful clinical tool for analyzing the T790M point mutation.